Two new species of Meliola from India - and A.K. DAS, T.K. JANA, S.N. GHOSH (Indian Phytopathology, 2005)
Two new species of Meliola Fries. collected from Nagaland (India) viz: M. holarrhenae-pubescens and M. gymnemae are described and illustrated in this paper.